A Literature Review on Global Challenges for Third Party Logistics (TPL or 3PL) - Hiran Gabriel, D. J.; Parthiban, M. (Asian Review of Mechanical Engineering, 2020)
Initially, all manufacturing industries had a separate logistics department of their own for the movement of their produced goods and services. This added to the complexity and cost to the industries since they had to maintain a huge workforce for the process. Thus, companies started hiring third parties for logistics purposes, these third parties are known as Third Party Logistics (TPL) or 3PLs. Nowadays every company employs TPLs for service to carry out shipments thus focussing on their core area of development than logistics. These 3PL firms face certain challenges globally in delivering services to their customers. The paper aims to have a systematic review of the challenges faced globally by 3PLs. The paper gathers information from many pieces of literature on three important challenges namely minimizing the lead time, adapting to the Industrial Dynamics, and adapting to the advancement in technologies. The review will be helpful for future scholars in listing the challenges faced by these industries globally.